Ask the Experts: How can the National Kidney Foundation''s Kidney Early Evaluation Program help to prevent/manage kidney disease in diabetic patients?. (July 2011) - Bomback, Andrew S; Whaley-Connell, Adam
Andrew S Bomback is Assistant Professor of Clinical Medicine at Columbia University College of Physicians and Surgeons (New York, NY, USA). He is a member of the steering committee of the National Kidney Foundation''s Kidney Early Evaluation Program (KEEP). He has published over 45 peer-reviewed articles on chronic kidney disease, diabetes and hypertension. He is principal investigator or co-investigator of more than ten ongoing clinical trials examining new treatments for kidney diseases, with a special focus on novel therapies for glomerular diseases. He is the co-author, with George Bakris, of the text, Chronic Kidney Disease and Hypertension Essentials . Adam Whaley-Connell is an Assistant Professor of Medicine at the University of Missouri-Columbia School of Medicine and the Harry S Truman VA Medical Center in the Division of Nephrology and Hypertension (MO, USA). He is an investigator of the Diabetes and Cardiovascular Center (MO, USA) and is involved in a translational program focused on mechanisms of early kidney injury. He currently serves as Vice-Chair for the National Kidney Foundation Kidney Early Evaluation Program.